PENGARUH PAJAK, TINGKAT KEPEMILIKAN ASING, RENCANA BONUS, DAN PERJANJIAN TERHADAP KEPUTUSAN HARGA TRANSFER - Ahmad Nurdin Hasibuan; Harisman Harisman; Abdul Wahab Samad (Jurnal Akuntansi, Keuangan, Pajak dan Informasi (JAKPI), 2022)
This study aims to determine the effect of Taxes, Foreign Ownership, Bonus Plans and Debt Covenants on the company's decision to transfer pricing to manufacturing companies listed on the Indonesia Stock Exchange in 2016 - 2019. The results show that taxes do not have a positive effect on companies to make transfers. Pricing because this is due to the number of companies to pay taxes every year. Foreign ownership has a positive effect, this is due to the large number of foreign institutions that have shares of more than 5% and 20% more. Bonus Plans have a positive effect, if their rewards or wages depend on reported bonuses on net income then it is possible to increase bonuses during the period by reporting net income as high as possible. Debt Covenant has a positive effect, this is because the calculation of the debt ratio shows that the maximum value is 1.06 and the average is 0.4356, indicating that almost half of the company's investment is in the form of debt. Simultaneously, taxes, foreign ownership, bonus plans and debt covenants have a significant effect on the company's decision to transfer pricing.